Effect of different extraction methods on the total phenolics of sugar cane products - Azlan, Azrina; Sultana, Sharmin; Mahmod, Ilya Iryani (Multidisciplinary Digital Publishing Institute, 2023)
The health benefits of sugar cane products are attributed to certain antioxidant compounds in plant materials. The presence of antioxidants in plant materials depends on the extraction method in terms of yield and the number of phenolic compounds identified. This study was carried out to evaluate the performance of the three extraction methods, which were selected from previous studies to show the effect of the extraction method on the content of antioxidant compounds in different types of sugar. This study also evaluates the potential of different sugar extracts in anti-diabetic activity based on in vitro assays (α-glucosidase and α-amylase). The results showed that sugar cane extracted with acidified ethanol (1.6 M HCl in 60% ethanol) was the best condition to extract a high yield of phenolic acids compared to other methods. Among the three types of sugar, less refined sugar (LRS) showed the highest yield of phenolic compounds, 57.72 µg/g, compared to brown sugar (BS) and refined sugar (RS) sugar, which were at 42.19 µg/g and 22.06 µg/g, respectively. Whereas, among the sugar cane derivatives, LRS showed minor and BS moderate inhibition towards α-amylase and α-glucosidase activity compared to white sugar (RS). Thus, it is suggested that sugar cane extracted with acidified ethanol (1.6 M HCl in 60% ethanol) is the optimum experimental condition for antioxidant content determination and provides a basis for further exploitation of the health-beneficial resources of the sugarcane products.